The role of polysaccharides from natural resources to design oral insulin micro- and nanoparticles intended for the treatment of Diabetes mellitus: A review - Meneguin, Andreia Bagliotti [UNESP]; Silvestre, Amanda Leticia Polli [UNESP]; Sposito, Larissa [UNESP]; Souza, Mauricio Palmeira Chaves de [UNESP]; Sabio, Rafael Miguel [UNESP]; Araujo, Victor Hugo Sousa [UNESP]; Cury, Beatriz Stringhetti Ferreira [UNESP]; Chorilli, Marlus [UNESP] (Elsevier B.V., 2021)
Oral administration of insulin (INS) would represent a revolution in the treatment of diabetes, considering that this route mimics the physiological dynamics of endogenous INS. Nano- and microencapsulation exploiting the advantageous polysaccharides properties has been considered an important technological strategy to protect INS against harsh conditions of gastrointestinal tract, in the same time that improve the permeability via transcellular and/or paracellular pathways, safety and in some cases even selectivity for targeting delivery of INS. In fact, some polysaccharides also give to the systems functional properties such as pH-responsiveness, mucoadhesiveness under specific physiological conditions and increased intestinal permeability. In general, all polysaccharides can be functionalized with specific molecules becoming more selective to the cells to which INS is delivered. The present review highlights the advances in the past 10 years on micro- and nanoencapsulation of INS exploiting the unique natural properties of polysaccharides, including chitosan, starch, alginate, pectin, and dextran, among others.
Keywords: Diabetes mellitus; Insulin; Polysaccharides; Microparticles; Nanoparticles; Oral route